2014
DOI: 10.1002/cne.23581
|View full text |Cite|
|
Sign up to set email alerts
|

Spine morphogenesis in newborn granule cells is differentially regulated in the outer and middle molecular layers

Abstract: New neurons are continuously added to the hippocampus of adult mammals. Their survival and integration into the circuitry are highly dependent on experience. Here we show that mushroom spine formation in newborn granule cells was modulated by experience and that dendritic segments in different areas of the molecular layer were differentially regulated. Specifically, spines of new neurons in the outer molecular layer of the dentate gyrus were more readily influenced by non-spatial features in the living environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 27 publications
2
27
1
1
Order By: Relevance
“…Interestingly, the heightened excitatory response in PAE‐EE mice was not associated with increased spine density. Previous studies have shown that neither EE, nor exercise, has a significant impact on total spine density in aDGCs, although both promote increased density of mushroom spines, which are thought to represent sites of enhanced excitatory synaptic transmission (Zhao et al, ; Piatti et al, ; Zhao et al, ). On the other hand, training on discrete spatial tasks stimulates enhanced dendritic complexity and spine density in aDGCs in proportion to the intensity of cognitive demand (Tronel et al, ; Lemaire et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the heightened excitatory response in PAE‐EE mice was not associated with increased spine density. Previous studies have shown that neither EE, nor exercise, has a significant impact on total spine density in aDGCs, although both promote increased density of mushroom spines, which are thought to represent sites of enhanced excitatory synaptic transmission (Zhao et al, ; Piatti et al, ; Zhao et al, ). On the other hand, training on discrete spatial tasks stimulates enhanced dendritic complexity and spine density in aDGCs in proportion to the intensity of cognitive demand (Tronel et al, ; Lemaire et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dendritic spine motility, total dendritic length, branch points, dendritic complexity, and mitochondria density are significantly higher in runners’ adult-born DG neurons for up to 3 weeks post-retroviral injection (Zhao et al 2006; Dietrich et al 2008; Steib et al 2014). However, by the fourth week, dendritic morphology and mitochondria content are indistinguishable from adult-born DG neurons in the sedentary brain (Zhao et al 2006, 2014; Steib et al 2014). Similar observations were made in a live imaging study in mice housed in an enriched environment containing running wheels (Gonçalves et al 2016).…”
Section: Exercise and The Hippocampusmentioning
confidence: 96%
“…Running may shorten the cell cycle of rapidly amplifying progenitor cells (Farioli-Vecchioli et al 2014; see, however, Fischer et al 2014) and accelerate neuronal maturation of adult-born DG neurons (Zhao et al 2006; Piatti et al 2011; Steib et al 2014). In particular, retroviral labeling studies (van Praag et al 2002; Zhao et al 2006) have shown that running promotes spine formation in the outer molecular layer of adult-born dentate granule cell dendrites (Zhao et al 2014). In addition, dendritic spine motility, total dendritic length, branch points, dendritic complexity, and mitochondria density are significantly higher in runners’ adult-born DG neurons for up to 3 weeks post-retroviral injection (Zhao et al 2006; Dietrich et al 2008; Steib et al 2014).…”
Section: Exercise and The Hippocampusmentioning
confidence: 99%
“…Spatial cues induce mushroom spine formation in the middle molecular layer of newborn neurons that receive inputs from the entorhinal cortex (EC) providing spatial information. Conversely, non-spatial components increase mushroom spine formation in the outer molecular layer receiving inputs from the lateral EC (Zhao et al 2014). Voluntary exercise affects dendritic complexity and spine density not only in the DG but also in afferent populations like pyramidal neurons in the CA1 and layer III pyramidal neurons of the entorhinal cortex (Redila and Christie 2006;Stranahan et al 2007).…”
Section: Exercise and Enriched Environment In Animals: From Cognitionmentioning
confidence: 98%